Benefits of Using the Learning Management System based on Flipped Learning Methodology - Santiago Pozo-Sánchez; Adrián Segura-Robles; Antonio José Moreno-Guerrero; Jesús López-Belmonte (Universidad Autónoma de Baja California, 2022)
AbstractAmong the different tools that can be used in the implementation of flipped learning, learning management systems stand out as one of the educational technology systems that best solve problems related to usability, accessibility, and evaluation. The objective of this study is to analyze the academic impact of flipped learning through LMS platforms versus the use of flipped learning in other non-interactive digital media, as traditional learning. For this, a quasi-experimental design was used in a sample of 231 Spanish secondary school students. A questionnaire was used to collect the data. The results show that students who have followed the teaching-learning process with flipped learning obtain better results than those who only apply the flipped learning method. It is concluded that the use of an LMS during the application of the flipped learning methodology contributes to an optimization of the general teaching-learning process.